BIOAVAILABILITY AND DISSOLUTION ENHANCEMENT OF GLYBURIDE NANOSUSPENSION - PRADEEP KUMAR M (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The main objective was to develop nanosuspension of glyburide (GLY) by quasi emulsification solvent diffusion method and to enhance dissolution and bioavailability characteristics of the drug GLY, an antidiabetic drug which belongs to Biopharmaceutical Classification System-II category. Materials and Methods: In this work, nanoparticles were prepared using polyvinyl alcohol, hydroxypropyl methyl cellulose, and Eudragit RL100. Twelve formulations of GLY (GLY-1–GLY-12) were formulated using the excipients at various compositions. Drug and excipient compatibility studies were conducted using Fourier transform infrared and differential scanning calorimeter. The prepared nanosuspension was analyzed using scanning electron microscopy for surface of the particle analysis, melting point, solubility, particle charge zeta (mv), percentage drug entrapment efficiency (%), and in vitro drug release. The optimized formulations of nanosuspension were further studied for in vivo pharmacokinetic evaluation. Reverse-phase high-performance liquid chromatography method was developed, validated, and used for the study of these formulations in rat plasma. Results: From these studies, it was confirmed that drugs and excipients chosen were compatible with each other. GLY-8 was the best formulation with a particle size of 85–96 nm with 168.7°C melting point, freely soluble in phosphate buffer pH 7.4, 93.53% drug entrapment, and 90.26±1 mV of zeta potential. This formulation shows percentage drug release of 99.85% in 24 h. In vivo pharmacokinetic study for optimized formulation (GLY -8) suggested that there was no reaction with the rat plasma. From the results, it was shown that Cmax and Tmax were found to be 0.604±0.03 μg/ml and 2±1.01 h, respectively. The values of t1/2 (h), area under the curve (AUC) (0-t), and AUC (0-∞) were found to be 10.04 h, 2.562±0.41 μg.h/ml, and 2.147±0.45 μg.h/ml, respectively. Conclusion: Based on the results obtained, oral administration of nanosuspension could not only provide the better absorption of poorly water soluble drugs but may also reduce toxicity and provide a new tool in drug delivery system.